Clinical effectiveness and cost-effectiveness of elemental nutrition for the maintenance of remission in Crohn’s disease: a systematic review and meta-analysis - Alexander Tsertsvadze; Tara Gurung; Rachel Court; Aileen Clarke; Paul Sutcliffe (Health Technology Assessment, 2015)
Background: Although enteral nutrition has been shown to be a viable treatment option for the management of active Crohn’s disease (CD), the evidence regarding its clinical benefits compared with standard treatments (e.g. steroids) for maintaining remission in patients with CD has been inconsistent. If enteral nutrition was to be effective, the use of drugs such as steroids and immunosuppressive drugs could be reduced, thereby reducing the likelihood of adverse events associated with these medications. Objectives: This systematic review aimed to assess the clinical effectiveness and cost-effectiveness of elemental nutrition (a type of enteral nutrition) for maintenance of remission in patients with CD. Data sources: Major bibliographic databases (e.g. MEDLINE, EMBASE, Cochrane Database of Systematic Reviews) were searched from inception to August/September 2013. Searches were not limited by study design, language or publication date. Websites for relevant organisations and references of included studies were checked. Methods: Experimental randomised and non-randomised controlled trials (RCTs and nRCTs) reporting clinical effectiveness and cost-effectiveness of elemental nutrition in the maintenance of remission in patients with CD were eligible. Study selection, data extraction and risk of bias (RoB) assessment were performed independently. Risk ratios (RRs) and mean differences (MDs) were pooled using a random-effects model. Heterogeneity was assessed via forest plots, Cochran’s Q and the I2 statistics. Overall, quality of evidence for each outcome was rated using the Grading of Recommendations, Assessment, Development, and Evaluation approach. Results: Eight studies (three RCTs and five nRCTs) were included in the review. RCTs indicated a significant benefit of elemental nutrition vs. no intervention (an unrestricted diet) in maintaining remission at 24 months [one RCT; RR 2.06, 95% confidence interval (CI) 1.00 to 4.43; very low-grade evidence] and preventing relapse at 12–24 months post baseline (two RCTs; pooled RR 0.57, 95% CI 0.38 to 0.84; I2 = 0%; high-grade evidence). Similarly, three nRCTs showed significant benefits of elemental nutrition over no intervention in maintaining remission at 12–48 months and preventing relapse at 12 months post baseline (MD 1.20 months, 95% CI 0.35 to 2.04 months). The incidence of mucosal healing was not significantly different in the intervention and control groups (RR 2.70, 95% CI 0.62 to 11.72). Adherence to an elemental nutrition regime was significantly worse than adherence to polymeric nutrition (RR 0.68, 95% CI 0.50 to 0.92) and, when compared with other active treatments (medications, polymeric nutrition or a combination), elemental nutrition yielded non-significant results with wide 95% CIs, rendering these results inconclusive. Complications and adverse events were too sparse to allow meaningful comparisons. None of the studies reported cost-effectiveness of elemental nutrition. Owing to scarcity of data, subgroup and sensitivity analyses could not be performed to explore methodological and clinical sources of heterogeneity. Limitations: The findings warrant cautious interpretation given the limitations of the evidence in methodological quality (small samples, short follow-up) and the RoB in individual studies (lack of blinding, confounding). Conclusions: Limited evidence indicates potential benefits of elemental nutrition against no intervention in the maintenance of remission and prevention of relapse in adult patients with CD. There was a lack or insufficient evidence on adverse events and complications. Future large and long-term randomised trials are warranted to draw more definitive conclusions regarding the effects of elemental nutrition in maintaining remission in CD. Trial registration: This study is registered as PROSPERO CRD42013005134. Funding: The National Institute for Health Research Health Technology Assessment programme.